Human resource management practices in building learning organizations: a study of large manufacturing organizations in Malaysia / Norashikin Hussein - Hussein, Norashikin (Institute of Graduate Studies, UiTM, 2013)
The rapidly changing business environment requires organizations to gain unique and sustainable competitive advantages over their competitors. Recognized as a source of competitive advantage, effective human resource management practices (HRM practices) clearly play a vital role in the success of any organization. As the knowledge economy demands for quality human resources, human resource management is called to play a more strategic role in facilitating learning in the organization, particularly in building learning organization. The objectives of this study are: (1) to examine the level of HRM practices in manufacturing organizations; (2) to investigate the relationships between HRM practices and building of learning organization; and finally (3) to examine leadership styles as moderator the relationship between HRM practices and building a learning organization. Based on the resource-based view theory, this study hypothesized that HRM practices would positively influence in the building of a learning organization. Data were collected using mail questionnaires sent to middle managers and nonexecutive employees of manufacturing organizations in Malaysia…